Down-regulation of 7SL RNA Expression and Impairment of Vesicular Protein Transport Pathways by Leishmania Infection of Macrophages - Misra, Smita (2005)
The parasitic protozoan Leishmania specifically manipulates the expression of host macrophage genes during initial interactions, as revealed by mRNA differential display reverse transcription-PCR and cDNA microarray analyses. The genes that are down-regulated in mouse (J774G8) or human (U937) macrophages upon exposure to Leishmania include small RNA transcripts from the short interspersed element sequences. Among the short interspersed element RNAs that are down-regulated is 7SL RNA, which is the RNA component of the signal recognition particle. Because the microbicidal functions of macrophages profoundly count on vesicular protein transport processes, down-regulation of 7SL RNA may be significant in the establishment of infection by Leishmania in macrophage phagolysosomes. To evaluate whether down-regulation of 7SL RNA results in inhibition of signal recognition particle-mediated vesicular protein transport processes, we have tested and found that the targeting of proteins to the endoplasmic reticulum and plasma membrane and the secretion of proteins by macrophages are compromised in Leishmania-infected J774G8 and U937 cells. Knocking down 7SL RNA using small interfering RNA mimicked the effect of exposure of macrophages to Leishmania. The overexpression of 7SL RNA in J774G8 or U937 cells made these cells resistant to Leishmania infection, suggesting the possible biological significance of down-regulation of 7SL RNA synthesis in the establishment of infection by Leishmania. We conclude that Leishmania down-regulates 7SL RNA in macrophages to manipulate the targeting of many proteins that use the vesicular transport pathway and thus favors its successful establishment of infection in macrophages.